Pengaruh Kepemimpinan Dan Komunikasi Internal Terhadap Produktivitas Karyawan KKSP - Lira Pirna; Yenni Del Rosa (GLOBAL SCIENTS PUBLISHER, 2026)
This study aims to examine and analyze the influence of leadership and internal communication on employee productivity at Koperasi Konsumen Keluarga Besar Semen Padang. The type of research used is associative research with a quantitative approach. The sample size of 135 respondents determined using probability sampling techniques. Data were processed using SPSS version 21 with multiple linear regression analysis. The results indicate that leadership has a positive and significant effect on employee productivity (t-value 4.001 > t-table 1.656). Similarly, internal communication has a positive and significant effect (t-value 5.765 > t-table 1.656). Simultaneously, both variables significantly influence productivity with an Adjusted R Square value of 0.533.